The correct answer is:
C
A bookstore is selling books for $10 each. Which graph shows the relationship between the number of books, x, the store sold and the total amount of money, y, paid from the book sales?
(1 point)
Responses
A
A
B
B
C
C
D
D
Skip to navigation
11 answers
When 1 cup of popcorn kernels are popped, they create 5 bowls of popped corn. How many bowls of popcorn would 8 cups of kernels produce?(2 points)
Responses
58 bowls
58 bowls
4 78 bowls
4 78 bowls
5 18 bowls
5 18 bowls
40 bowls
Responses
58 bowls
58 bowls
4 78 bowls
4 78 bowls
5 18 bowls
5 18 bowls
40 bowls
The correct answer is:
40 bowls
40 bowls
Rebecca bought a video game in Miami. The game was $30. Miami has a 7% sales tax. How much money did Rebecca pay for the video game including sales tax?(2 points)
Responses
$32.10
$32.10
$33.50
$33.50
$37.00
$37.00
$51.00
Responses
$32.10
$32.10
$33.50
$33.50
$37.00
$37.00
$51.00
To calculate the total amount Rebecca paid for the video game including sales tax, we need to add the sales tax to the original price of the game.
Sales tax amount = 7% of $30 = 0.07 * $30 = $2.10
Total amount paid = $30 + $2.10 = $32.10
Therefore, Rebecca paid $32.10 for the video game including sales tax.
The correct answer is:
$32.10
Sales tax amount = 7% of $30 = 0.07 * $30 = $2.10
Total amount paid = $30 + $2.10 = $32.10
Therefore, Rebecca paid $32.10 for the video game including sales tax.
The correct answer is:
$32.10
Write the following expression using the fewest possible terms:
( 5 + 38
y) + ( 14
y - 2)
(1 point)
Responses
18 y − 3
18 y − 3
18 y + 3
18 y + 3
58 y − 3
58 y − 3
58 y + 3
( 5 + 38
y) + ( 14
y - 2)
(1 point)
Responses
18 y − 3
18 y − 3
18 y + 3
18 y + 3
58 y − 3
58 y − 3
58 y + 3
To simplify the given expression, we can combine like terms.
(5 + 38y) + (14y - 2)
= 5 + 38y + 14y - 2
= (38y + 14y) + (5 - 2)
= 52y + 3
Therefore, the expression can be written as:
52y + 3
The correct answer is:
52y + 3
(5 + 38y) + (14y - 2)
= 5 + 38y + 14y - 2
= (38y + 14y) + (5 - 2)
= 52y + 3
Therefore, the expression can be written as:
52y + 3
The correct answer is:
52y + 3
Simplify the expression.
(7𝑥 + 6) ― (8 + 𝑥)
(2 points)
Responses
8x - 2
8x - 2
7x - 48
7x - 48
8x - 14
8x - 14
6x - 2
(7𝑥 + 6) ― (8 + 𝑥)
(2 points)
Responses
8x - 2
8x - 2
7x - 48
7x - 48
8x - 14
8x - 14
6x - 2
To simplify the given expression, we need to distribute the negative sign to both terms inside the parentheses.
(7x + 6) - (8 + x)
= 7x + 6 - 8 - x
= 7x - x + 6 - 8
= 6x - 2
Therefore, the simplified expression is:
6x - 2
The correct answer is:
6x - 2
(7x + 6) - (8 + x)
= 7x + 6 - 8 - x
= 7x - x + 6 - 8
= 6x - 2
Therefore, the simplified expression is:
6x - 2
The correct answer is:
6x - 2
Select ALL equivalent expressions to:
(7𝑥 ― 2) ― (0.04𝑥 ― 3 + 0.2𝑥)
(2 points)
Responses
(7x −
2) −
(0.24x −
3)
(7x negative 2) negative (0.24x negative 3)
7.16x −
5
7.16x negative5
6.76x +
1
6.76x plus 1
5.76x
5.76x
7.76x
(7𝑥 ― 2) ― (0.04𝑥 ― 3 + 0.2𝑥)
(2 points)
Responses
(7x −
2) −
(0.24x −
3)
(7x negative 2) negative (0.24x negative 3)
7.16x −
5
7.16x negative5
6.76x +
1
6.76x plus 1
5.76x
5.76x
7.76x
To simplify the given expression, we need to combine like terms within each parentheses and then simplify further.
(7x - 2) - (0.04x - 3 + 0.2x)
= 7x - 2 - 0.04x + 3 - 0.2x
= 7x - 0.04x - 0.2x - 2 + 3
= 7x - 0.24x - 2 + 3
= 7x - 0.24x + 1
Therefore, the simplified expression is:
7x - 0.24x + 1
The only equivalent expression from the given options is:
(7x - 2) - (0.24x - 3)
None of the other options provided are equivalent expressions.
(7x - 2) - (0.04x - 3 + 0.2x)
= 7x - 2 - 0.04x + 3 - 0.2x
= 7x - 0.04x - 0.2x - 2 + 3
= 7x - 0.24x - 2 + 3
= 7x - 0.24x + 1
Therefore, the simplified expression is:
7x - 0.24x + 1
The only equivalent expression from the given options is:
(7x - 2) - (0.24x - 3)
None of the other options provided are equivalent expressions.